“LOLOS DARI TERKAMAN BATARA KALA” Elaborasi Filosofis Mitos Batara Kala dalam Ruwatan Jawa - Armada Riyanto (Studia Philosophica et Theologica, 2006)
Myth of Murwakala in Javanese Ruwatan addresses fundamental human questions about the origin and arbitrary nature of evil. It tells how the monster Kala, born from the spilt seed of the god Guru, becomes a danger to mankind when he appetites for human flesh. Dalang Kandhabuwana, an incarnation of the god Wisnu, challenges the monster and ultimately neutralizes him by reading from his body the secret words inscribed upon it earlier by the god Guru. A Ruwatan based on the Birth of Batara Kala myth always contains, in some form, these two elements: a presentation of the Kala story; and prayers from a corpus of old and obscure mantras. This article studies philosophically the myth of Batara Kala and its origins discovered in the old Javanese literatures. It elaborates (1) what is myth, (2) the myth of Batara Kala, (3) symbolism of Batara Kala, (4) origins of Batara Kala in Javanese literatures, (5) concluding remarks. The understanding of myth is explored from Schelling’s philosophy, whereas myth of Batara Kala is taken from the Old Literatures of Sastra Parwa and Tantu Panggelaran, as well as from Indian Hinduism’s epistemology. At the end of elaboration I will offer some concluding remarks on Ruwatan in crystalized points of ideas.